2013
DOI: 10.1108/00021461311321311
|View full text |Cite
|
Sign up to set email alerts
|

Financial performance of publicly‐traded agribusinesses

Abstract: Structured Abstract:Purpose -Agribusinesses represent a fundamental link in connecting farmers with retailers and consumers, yet little research has been done to examine the historical financial performance of these food processing firms.Design/methodology/approach -Our research examines how publicly-traded agribusinesses perform financially compared to all firms over the period from 1961 to 2011. We utilize several indicators of company success, including financial ratios and balance sheet/income statement it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 21 publications
6
44
2
2
Order By: Relevance
“…[133] suggested that financial performance is usually measured using the following: return on assets (ROA), return on equity (ROE), return on investment (ROI), profit margin, earning per share, and value per employee. However, [134] reported that ROA and ROE are considered to be the most popular means for measuring a firm's financial performance. It must be noted that focusing solely on financial performance as a measure of organizational performance is not enough to improve financial results [121].…”
Section: Financial Performancementioning
confidence: 99%
“…[133] suggested that financial performance is usually measured using the following: return on assets (ROA), return on equity (ROE), return on investment (ROI), profit margin, earning per share, and value per employee. However, [134] reported that ROA and ROE are considered to be the most popular means for measuring a firm's financial performance. It must be noted that focusing solely on financial performance as a measure of organizational performance is not enough to improve financial results [121].…”
Section: Financial Performancementioning
confidence: 99%
“…Delen, Kuzey, and Uyar (2013) indicate that the most significant variables in forecasting future returns is net profit margin ratio and earnings before interest and tax to equity ratio. Katchova and Enlow (2013) evaluate Du Pont ratios to compare return on equity components among agri-businesses and all companies. The results of Du Pont ratios show that agri-businesses outperform at the median the sample of all companies in terms of financial ratios associated with liquidity, market ratios, and profitability, but had marginally lower debt ratios and liquidity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Publicly-traded agribusinesses are defined as those that are publicly listed. Such firms have greater access to financing, because they can issue more stock, but are also subject to more regulation (Katchova and Enlow, 2013). Literature review shows, that such firms operate similarly to other public firms, thus allowing to apply Altman's model.…”
Section: General Overview Of Agricultural Sectormentioning
confidence: 99%
“…Robelo (2012) has evaluated the risk of insolvency for Portuguese agricultural credit cooperatives, and identified the main determinants of failure: customer base growth, transformation ratio, credit overdue, expenses ratio, structural costs, liquidity, indebtedness, and financial margin. Katchova and Enlow (2013) explored historical financial performance of publicly traded US agribusinesses and revealed that agribusinesses outperform that median sample of firms in terms of profitability, liquidity, operating efficiency and market ratios, but show lower liquidity and debt ratios. Lukason (2014) has investigated failure process and causes in the Estonian agricultural sector.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation